Método de apontamento e cálculo de perdas produtivas para compor OEE em uma empresa metalúrgica - Sonoda, Gustavo Yano (2020)
The current scenery of the global industry has been highlighted by a continuous chase to achieve cost reductions. A way to reach cost reductions is by improving the performance of the equipment, along with decreasing production losses. The initial step chosen by most companies globally is the implementation of methods or tools to identify losses and measure the performance. This paper presents the improvements within the OEE (Overall Equipment Effectiveness) results in the stage after the implementation of methodologies that involves diary OEE follow-ups and improvement analysis triggers in a metallurgical industry. Therefore, QRQC (Quick Response Quality Control) and Lean Manufacturing methods has been implemented to do daily follow-ups and improvements. Regarding the results, it was noticeable that the implementation of the OEE and the methodologies affected the company results in a positive way.